Training effects of affordance judgments in four different settings: towards developing a training battery for affordance judgments - Milena S. Gölz; Isabel Bauer; Lisa Finkel; Cedric Rosati; Andrea Wenzel; Tobias Herrmann; Kenneth F. Valyear; Jennifer Randerath (Experimental Brain Research, 2025)
Training affordance judgments (AJs) across different settings, such as judging whether an object is within reach or an obstacle conquerable, could be meaningful to older adults and neurological patients with diminished judgment behaviors. The long-term aim is to develop a comprehensive training battery with different types of AJ tasks. The present study used a between-subjects design to evaluate trainability in four different settings. Judgment behavior of 52 healthy young adults was trained (80 trials) in one out of four settings (per trained task N = 13): 1. Reaching horizontally forward for an object, 2. Fitting one hand horizontally into an aperture, 3. Fitting upright under a horizontal barrier, and 4. Stepping over a hurdle. Participants’ judgment performance was assessed pre- versus post-training. Additionally, to assess whether other AJ-based tasks as potential distractors may override training effects, the other three non-trained tasks were presented, and subsequently, judgment performance in the trained task was assessed once more. Accuracy, judgment tendency, and perceptual sensitivity served as dependent variables. A Friedman Test revealed a main effect of time point in all three variables. Post hoc analyses showed significant improvements in the trained task even after exposure to other AJ tasks. The results suggest that in young healthy adults, AJs can be trained effectively within different AJ settings, and improvements within one setting can last, even when AJs in other settings are solved in between. Our study provides proof of principle and an important step towards developing a training battery for AJs.

To use or to move: goal-set modulates priming when grasping real tools - Kenneth F. Valyear; Craig S. Chapman; Jason P. Gallivan; Robert S. Mark; Jody C. Culham (Experimental Brain Research, 2011)